Implementasi M-commerce pada Toko Hijab dengan Menggunakan Personal Extreme Programming - Yudi Ananta Prasetya; Wildan Suharso; Gita Indah Marthasari (Universitas Muhammadiyah Malang, 2023)
Rumah Muslimah is a hijab shop that is engaged in fashion. Some of the problems experienced by Rumah Muslimah are the conventional ordering system and the inadequate promotion system. Therefore, Rumah Hijab requires an application that can be accessed by all its customers and can also be a tool to facilitate transactions between cities. The development method used in this research is Personal Extreme Programming (PXP). PXP is a development inherited method of Extreme Programming (XP). The application that will be built in this research is a mobile-based store application. The first phase that is carried out is the need, namely looking for the requirements needed to create an application. The next stage is to determine the priority of a feature with the client. Development will be carried out according to the iterations that have been determined together. The result of this research is that PXP can be applied in the development of mobile applications for Rumah Muslimah. The ability and experience of programmer will greatly affect the duration of the work.